2015
DOI: 10.1016/j.nicl.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory behavioral control: A stochastic dynamic causal modeling study comparing cocaine dependent subjects and controls

Abstract: Cocaine dependence is associated with increased impulsivity in humans. Both cocaine dependence and impulsive behavior are under the regulatory control of cortico-striatal networks. One behavioral laboratory measure of impulsivity is response inhibition (ability to withhold a prepotent response) in which altered patterns of regional brain activation during executive tasks in service of normal performance are frequently found in cocaine dependent (CD) subjects studied with functional magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 121 publications
(191 reference statements)
1
28
0
Order By: Relevance
“…All these effective connectivities had positive strength except for the connectivity from insula to medial frontal cortex. Consistent with the triple-system theory [78], these effective connectivity studies indicated that CD is associated with an imbalance among the PFC regions, insula, and striatal regions: weakened control of the PFC regions over the striatal regions during working memory [16] and response inhibition [17] and strengthened control of the striatal and insular regions over the PFC regions during the cocaine-Stroop task [18]. …”
Section: Task-based Brain Connectivity Studies In Humansmentioning
confidence: 57%
See 2 more Smart Citations
“…All these effective connectivities had positive strength except for the connectivity from insula to medial frontal cortex. Consistent with the triple-system theory [78], these effective connectivity studies indicated that CD is associated with an imbalance among the PFC regions, insula, and striatal regions: weakened control of the PFC regions over the striatal regions during working memory [16] and response inhibition [17] and strengthened control of the striatal and insular regions over the PFC regions during the cocaine-Stroop task [18]. …”
Section: Task-based Brain Connectivity Studies In Humansmentioning
confidence: 57%
“…Three effective connectivity studies were conducted to investigate neural correlates underlying working memory [16], response inhibition [17], and cue reactivity [18] in CDs. Ma et al [16] used dynamic causal modeling (DCM) of a working memory task and found that during short memory delay condition, the inferior frontal gyrus to striatum effective connectivity was reduced in CDs but increased in CTLs.…”
Section: Task-based Brain Connectivity Studies In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the SIB allowed us to investigate whether excessive premature responding and corresponding brain activations constitutes a vulnerability factor preceding drug use (Just et al, ). Given the importance of the striatum to top‐down control and reward processing in addiction and its abnormal neuronal connectivity with the PFC (Ma et al, 2014; Ma et al, ), we also investigated the selective involvement of this region and its effective connectivity using dynamic causal modeling (DCM) within key nodes of the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Using a stochastic dynamic causal modeling (DCM) approach, Ma et al (2014) showed that cocaine subjects differed from controls in that effective connectivity from inferior frontal cortex to striatum was less affected by an immediate working memory task in the cocaine compared to the control group, and the effective connectivity from middle frontal gyrus to the striatum was less affected by the delayed working memory task in the cocaine compared to the control group. And Ma et al (2015) utilized an fMRI-based stochastic DCM to study the effective neuronal connectivity associated with response inhibition in cocaine dependent subjects, elicited under performance of a Go/NoGo task with two levels of NoGo difficulty (Easy and Hard). The DCM analysis revealed that prefrontal-striatal connectivity was influenced during the NoGo conditions for both groups.…”
Section: Introductionmentioning
confidence: 99%